2018
DOI: 10.18044/medinform.201853.926
|View full text |Cite
|
Sign up to set email alerts
|

Virology and histopathology in patients with chronic hbv infection in bulgaria

Abstract: The histopathology of hepatitis B is diverse and reflects the natural history of chronic HBV-infection. Liver biopsy is gold standard for assessment of disease-activity and fibrosis. Treatment-decision is based on the assessment of liver disease severity as well as on patient's age, viral load, and HBeAg status. The relationship between these parameters and liver histopathology is not studied in details. We analysed treatment-naïve patients from single canter: 231 with histologically-proven chronic hepatitis B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…In Bulgaria, HDV genotyping has only been analysed in a few studies, and HDVgenotype 1 was found to be prevalent, similar to the other neighbouring countries [44]. We conducted an investigation among 12 Bulgarian chronic HDV patients, aged 28 to 62 years, during the period of 2013-2019.…”
Section: Prevalent Hdv Genotypes and Their Pathogenicitymentioning
confidence: 97%
See 2 more Smart Citations
“…In Bulgaria, HDV genotyping has only been analysed in a few studies, and HDVgenotype 1 was found to be prevalent, similar to the other neighbouring countries [44]. We conducted an investigation among 12 Bulgarian chronic HDV patients, aged 28 to 62 years, during the period of 2013-2019.…”
Section: Prevalent Hdv Genotypes and Their Pathogenicitymentioning
confidence: 97%
“…In 1986, Naoumov and colleagues reported the prevalence of delta infection among 105 HBsAg-positive patients with chronic liver diseases and 42 patients who had died due to fulminant hepatitis B. Delta infection was detected in 8.6% of subjects with chronic HBV infection and 7.1% of patients with fulminant hepatitis [42]. During the period of 1986-1997, Krastev and colleagues found the rate of HDV infection to be 16.1% higher among patients in hepatology clinics, with a high concentration of patients with chronic HBV and HDV infection [44]. In 1998, B. Iliev and colleagues reported that of 1465 HBsAg-positive serum samples, 151 (10.3%) were positive for delta infection.…”
Section: Epidemiology Of Hdv In General and Hepatology Clinic Populat...mentioning
confidence: 99%
See 1 more Smart Citation